Monosaccharides Dehydration Assisted by Formation of Borate Esters of α-Hydroxyacids in Choline Chloride-Based Low Melting Mixtures - Istasse, Thibaut; Lemaur, Vincent; Debroux, Gwénaëlle; Bockstal, Lauris; Lazzaroni, Roberto; Richel, Aurore (Frontiers in Chemistry, 2020)
The synthesis of 5-hydroxymethylfurfural (5-HMF) and 2-furfural (2-F) by hexoses and pentoses dehydration is considered as a promising path to produce materials from renewable resources. Low-transition-temperature mixtures (LTTMs) enable selective (> 80%) dehydration of ketoses to furanic derivatives at moderate temperature (< 100°C). However, aldoses dehydration generally requires higher temperatures and an isomerization catalyst. Chromium trichloride has been reported as one of the most efficient catalyst but its kinetic inertness could limit its performances below 100°C. Consequently, we investigate herein boric acid catalysis of aldoses dehydration in LTTMs based on choline halides and organic acids at 90°C. The limited activity of boric acid regarding furanic compounds synthesis (e.g. 5% 5-HMF yield and 23% glucose conversion after one hour at 90°C with maleic acid) can be enhanced through tetrahydroxyborate esters (THBE) formation with α-hydroxyacids (e.g. 19% 5-HMF yield and 61% glucose conversion after one hour at 90°C). THBE formation is however associated with H3O+ generation favoring the appearance of side products (humins). We demonstrate that boric acid catalysis is not straightforward and that the use of THBE under moderate acidity should be further investigated to limit humins formation and promote furanic derivatives synthesis.